Measuring health outcomes and experiences from a patient’s perspective - Coelho, Anabela (2022)
The primary objective of health systems is to improve people's health and well-being. Yet, health systems today face significant challenges, ranging from delivering high-quality care to tackling inequalities in health outcomes, getting rid of ineffective care, and investing more in health systems' resilience. Faced with those challenges, the ability to assess whether health systems are successful in delivering good health outcomes and experiences for the people they serve is critical. Health systems are awash with data. There are good measures of what providers can do and the resources this takes – think of the many administrative data about healthcare activities, costs, inputs, outcomes measuring mortality, and incidence and prevalence of diseases. Yet far too little is known about how healthcare impacts the lives of people. This makes it difficult to gain insight into the effectiveness of the healthcare and assess how policy change contributes to improvement in health outcomes.